Nanotribology of Ionic Liquids: Transition to Yielding Response in Nanometric Confinement with Metallic Surfaces - Antoine Lainé (American Physical Society, 2020)
Room-temperature ionic liquids (RTILs) are molten salts which exhibit unique physical and chemical properties, commonly harnessed for lubrication and energy applications. The pure ionic nature of RTIL leads to strong electrostatic interactions among the liquid, furthermore exalted in the presence of interfaces and confinement. In this work, we use a tuning-fork-based dynamic surface force tribometer, which allows probing both the rheological and the tribological properties of RTIL films confined between a millimetric sphere and a surface, over a wide range of confinements. When the RTIL is confined between metallic surfaces, we see evidence of an abrupt change of its rheological properties below a threshold confinement. This is reminiscent of a recently reported confinement-induced capillary freezing, here observed with a wide contact area. In parallel, we probe the tribological response of the film under imposed nanometric shear deformation and unveil a yielding behavior of the interfacial solid phase below this threshold confinement. This is characterized by a transition from an elastic to a plastic regime, exhibiting striking similarities with the response of glassy materials. This transition to yielding of the RTIL in metallic confinement leads overall to a reduction in friction and offers a self-healing protection of the surfaces avoiding direct contact, with obvious applications in tribology.